Mechanical bridge to heart transplantation - Nikonenko, A. S.; Tanskyi, V. G. (Modern medical technology, 2019)
Purpose of the study. The purpose of the work is to assess the effectiveness of using mechanical support for blood circulation in potential cardiac recipients who need urgent transplantation. Material and methods. The study included 47 patients and divided into two groups. The first group included 8 potential cardiac recipients, who had established mechanical support for the BiVAD blood flow. The second group included 39 potential cardiac recipients, who had LVAD’s mechanical support for the circulatory system. The main disease that led to the development of terminal congestive heart failure was dilated cardiomyopathy. The INTERMACS scale was used to assess the patient’s status. A Scale for the Classification of Patients with Progressive Heart Failure. We used the UNOS scale to assess the status of the patient who needed orthotopic cardiac transplantation. The algorithm of the Thoracic Committee of a single size distribution of organs for determining the urgent implementation of cardiac transplantation. Results and discussion. Biventricular support is necessary for patients with high central venous pressure, increased pulmonary vascular resistance or with malignant arrhythmias, resistant to drug therapy. For the purpose of the final therapy and biventricular support, the system of choice can be a fully artificial heart. Conclusions. Indications for biventricular circulation support are pronounced hemodynamic manifestations of impaired pumping function of the right and left ventricles of the transplanted heart. Systems DK (VAD) is the most effective «bridge to transplantation». It is important to choose the device for the patient, not the patient for the device.